(untitled) (Hungarian Journal of Industry and Chemistry, 2010)
This paper summarises and presents the dominant processes with a geometrically non-defined cutting edge. The review reflects on the methods of generating and profile gear grinding applied in these days industry. The analyses of the machine tools applied in several processes include functionality, machining quality, productivity and economy. I summarize the most important innovations linked to the elements of the manufacturing system, highlighting the economical application of galvanic bonded CBN grinding wheels trough the combination of processes. I display the processes and tools fexibility, productivity and it’s field of application.